Comparing the most demanding scenarios of official matches across five different professional team sports in the same club - Franc García; Daniel Fernández; Jordi Illa; Xavier Reche; Roger Font; Marc Guitart; Francesc Pla; Joan Ramon Tarragó; Jairo Vázquez-Guerrero (Elsevier, 2022)
Introduction: The purpose of this study was to compare the most demanding scenarios (MDS) of match-play across five different team sports of the same club (basketball, futsal, handball, rink hockey and soccer) during five different time epochs (30, 60, 120, 180 and 300 s). Material and methods: Sixty-five professional male players were monitored across 14 to 17 official matches via a local positioning system. Peak physical demands included total distance, distance, and actions >18 km·h−1 and distance and number of accelerations and decelerations >2 m·s−2. One-way analysis of variance and Tukey post-hoc tests were used to test statistical significance (p <.05), whereas standardized Cohen's effect size and the respective 95% confidence intervals were calculated to detect differences between team sports. Results: While soccer and rink hockey achieved the greatest MDS in total distance, and distance and number of actions >18 km·h−1 during all the time epochs examined, basketball presented the highest peak values in number of accelerations and decelerations >2 m·s−2 during 30-s and 60-s time epochs. Conclusion: In conclusion, the MDS during competition are significantly different across team sports, which can be useful in determining the upper limit threshold for sport-specific training optimisation and return to play purposes.